Kontribusi Ilmu Nahwu dan Shorof Terhadap Kemampuan Pemahaman Tafsir Al-Qur’an: Studi pada Peserta MTQ Cabang Tafsir Bahasa Arab - Nur Balqhis Dwi Putriyana; Kamal Yusuf (MAN 4 Kota Pekanbaru, 2025)
This study examines the influence of Nahwu (syntax) and Shorof (morphology) on Qur’anic interpretation skills among participants of the Musabaqah Tilawatil Qur’an (MTQ) in Arabic tafsir category. Using a descriptive qualitative design, the research was conducted at the East Java LPTQ for one semester (four months) and involved three informants (two participants and one coach) through in-depth interviews. Data were analyzed thematically using coding and category consolidation. The findings identify a three-fold thematic model in which grammatical mastery enhances interpretive performance through (1) increased confidence in articulating syntactic reasoning, (2) improved accuracy in i’rab, and (3) more coherent structural mapping of verses. Limited training time and uneven coaching intensity emerge as major constraints. The study contributes a preliminary conceptual model linking levels of Nahwu-Shorof proficiency with MTQ tafsir performance, offering an empirical basis for evaluating and structuring future MTQ training programs.